SOSIALISASI PASAR DIGITAL PADA PEDAGANG GROSIR DESA MEUNASAH ALUE KOTA LHOKSEUMAWE - Fuadi; Razali, Ramadhan (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2022)
Digital marketing has an important role in achieving more modern marketing goals. This is because digital marketing is a quality way of working and is based on meaningful values, and provides motivation and inspiration for better marketing. Digital marketing is a marketing activity including branding that uses various web-based media such as blogs, websites, e-mail, or social networks. This dedication aims to provide understanding to the community about marketing through digital marketing. The object of this dedication is the village community of Meunasah Alue, District. Muara Dua, Lhokseuamawe City. While the result found is that the empowerment of micro-businesses in the village of Meunasah Alue is very effective and efficient. This is because the color of the diversity of the micro business itself.